(untitled) (Journal of Information Technologies in Education (ITE), 2015)
Relevant for teaching modern science and practice is the task of finding ways to increase motivation, learning by intensifying qualitatively new teaching tools, design and implementation of technological approach to professional training of teachers, especially primary school teacher. The article summarizes the views of scientists on the use of design technology in higher pedagogical educational institution, organization design expediency of future teachers as an example of discipline "Mathematics". Design and technological approach allows for potential developmental math through a combination of formal mathematical knowledge of the emotional and aesthetic component of their production, with the formation of subjective attitude towards new knowledge. Thus, the creation of the "World Geometry" not only promotes the popularization of science, but also influences the outlook of the future teacher, his adaptability and mobility in the modern educational environment, fundamentalization his training.